Retinal inhibition of glycogen synthase kinase 3 beta protects against tau phosphorylation and stabilises microtubule assembly: Molecular and cell biology/neurodegeneration and neuroprotection. (7th December 2020) - Chitranshi, Nitin; Rajput, Rashi; Garthwaite, Linda; Thananthirige, Kanshika Pushpitha Maha; Mirzaei, Mehdi; Sheriff, Samran; Godinez, Angela; Gupta, Veer; Graham, Stuart; Gupta, Vivek K.
Abstract: Background: The microtubule associated protein tau is known to have several important functions like assembly and stabilisation of microtubules, axonal transport and neurite outgrowth in neurodegenerative diseases. Gsk3β, glycogen synthase kinase, plays a key role in regulating tau protein activity. There is little understanding of tau and Gsk3β association in the neurogenerative disorders affecting retina. Shp2, the mitogenic phosphatase, is associated with regulation of growth factor signalling pathways in the central nervous system. In this study we demonstrate that Gsk3β inhibition can suppress tau hyperphosphorylation and rescue the inner retinal degenerative changes induced by Shp2 overexpression (OE). Methods: Adult Sprague‐Dawley rats were subjected to intravitreal injection of adeno‐associated viral vector (AAV2) overexpressing either Shp2 or eGFP alone (3.4x10 12 GC/ml; n=8). These animals were also subjected to weekly (8 weeks) intravitreal injections of Gsk3β inhibitor (10 nM) and control. Electrophysiology and positive scotopic threshold response (pSTR) (‐4.3 log cd s/m 2 ) were measured using Phoenix Ganzfield two months following intra‐ocular injections. The amplitude of each component was measured and analysed. Immunohistochemistry (IHC) and Western blot (WB) were performed for pTau Ser 404, Tau, pGsk3β Ser 9, Gsk3β, Ac‐tubulin and Tyr‐tubulin. Results: Shp2OE in the rat eye significantly reduced the pSTR amplitudes (44%±3.1%) compared to PBS and GFP control. However, animals treated with Gsk3β inhibitor in Shp2OE retina demonstrated significant protection of pSTR amplitudes (81±5 % protection; n=32, p<0.05). IHC analysis demonstrated increased pTau Ser 404 and decreased pGsk3β Ser 9 immunoreactivity in the Shp2OE RGCs whereas pharmacological inhibition of Gsk3β for 8 weeks reversed the phosphorylation status of tau and Gsk3β in animals recieving AAV‐Shp2. We found that Shp2OE led to a markedly reduced expression of Ac‐tubulin (stable microtubules) and increased expression of Tyr‐tubulin (unstable microtubules) compared with control retina. Remarkably, the effects of Shp2OE on microtubules assembly was reversed upon Gsk3β inhibitor administration. Conclusion: Shp2OE in the retina led to abnormal tau hyperphosphorylation via Gsk3β activation causing deficits in RGCs visual function through the disruption of microtubular assembly. Shp2 may thus be an attractive therapeutic target to counter RGC neurodegeneration by reducing tau hyperphosphorylation in Alzheimer's disease.